Electron collisions with ArH+ molecular ions: highly excited vibrational states and dissociative excitation. (1st November 2022) - Djuissi, E; Bultel, A; Tennyson, J; Schneider, I F; Laporta, V
Abstract: A theoretical investigation of dissociative recombination and dissociative excitation processes involving electron collisions with the argonium ion (ArH + ) at energies up to 7 eV is presented. Curves and couplings obtained using R-matrix calculations are used to provide the input for molecular dynamics calculations based on the multichannel quantum defect theory. A full set of vibrationally resolved cross sections and rate coefficients is presented for the kinetic modeling of argon-containing non-equilibrium plasma.